The Employment Precariousness Scale (EPRES): psychometric properties of a new tool for epidemiological studies among waged and salaried workers. Issue 8 (24th June 2010) - Vives, Alejandra; Amable, Marcelo; Ferrer, Montserrat; Moncada, Salvador; Llorens, Clara; Muntaner, Carles; Benavides, Fernando G; Benach, Joan
Abstract : Background: Despite the fact that labour market flexibility has resulted in an expansion of precarious employment in industrialised countries, to date there is limited empirical evidence concerning its health consequences. The Employment Precariousness Scale (EPRES) is a newly developed, theory-based, multidimensional questionnaire specifically devised for epidemiological studies among waged and salaried workers. Objective: To assess the acceptability, reliability and construct validity of EPRES in a sample of waged and salaried workers in Spain. Methods: A sample of 6968 temporary and permanent workers from a population-based survey carried out in 2004–2005 was analysed. The survey questionnaire was interviewer administered and included the six EPRES subscales, and measures of the psychosocial work environment (COPSOQ ISTAS21) and perceived general and mental health (SF-36). Results: A high response rate to all EPRES items indicated good acceptability; Cronbach's α coefficients, over 0.70 for all subscales and the global score, demonstrated good internal consistency reliability; exploratory factor analysis using principal axis analysis and varimax rotation confirmed the six-subscale structure and the theoretical allocation of all items. Patterns across known groups and correlation coefficients with psychosocial work environment measures and perceived health demonstrated the expected relations, providing evidence of construct validity. Conclusions: Our results provide evidence in support of the psychometric properties of EPRES, which appears to be a promising tool for the measurement of employment precariousness in public health research.